2009
DOI: 10.1371/journal.pone.0006489
|View full text |Cite
|
Sign up to set email alerts
|

No Benefit from Chronic Lithium Dosing in a Sibling-Matched, Gender Balanced, Investigator-Blinded Trial Using a Standard Mouse Model of Familial ALS

Abstract: BackgroundIn any animal model of human disease a positive control therapy that demonstrates efficacy in both the animal model and the human disease can validate the application of that animal model to the discovery of new therapeutics. Such a therapy has recently been reported by Fornai et al. using chronic lithium carbonate treatment and showing therapeutic efficacy in both the high-copy SOD1G93A mouse model of familial amyotrophic lateral sclerosis (ALS), and in human ALS patients.Methodology/Principal Findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 17 publications
3
77
0
Order By: Relevance
“…In this regard, a recent study did not identify any therapeutic benefit of chronic lithium treatment with respect to disease onset, progression of neurological symptoms, or survival duration in a mouse model (73). Interestingly, and in good agreement with our study, the study found evidence for early onset of low-grade neurological symptoms and signs of less-effective body weight maintenance (73). Regarding lithium clinical trials for AD (19,23,74), frequent extrapyramidal side effects were already detected in a pilot study (22), and a recent study of the feasibility and tolerability of lithium therapy in AD patients reports high rates of discontinuation due to the high incidence of lithium toxicity in the elderly (19).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In this regard, a recent study did not identify any therapeutic benefit of chronic lithium treatment with respect to disease onset, progression of neurological symptoms, or survival duration in a mouse model (73). Interestingly, and in good agreement with our study, the study found evidence for early onset of low-grade neurological symptoms and signs of less-effective body weight maintenance (73). Regarding lithium clinical trials for AD (19,23,74), frequent extrapyramidal side effects were already detected in a pilot study (22), and a recent study of the feasibility and tolerability of lithium therapy in AD patients reports high rates of discontinuation due to the high incidence of lithium toxicity in the elderly (19).…”
Section: Discussionmentioning
confidence: 95%
“…Regarding the ongoing clinical trials of lithium for ALS (71), it will be of particular interest to see whether the potential observed in the initial study (70) is confirmed, given the well-known role of Fas signaling in mediating apoptotic death of ALS spinal motoneurons (72). In this regard, a recent study did not identify any therapeutic benefit of chronic lithium treatment with respect to disease onset, progression of neurological symptoms, or survival duration in a mouse model (73). Interestingly, and in good agreement with our study, the study found evidence for early onset of low-grade neurological symptoms and signs of less-effective body weight maintenance (73).…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, other groups attempted to reproduce the preclinical data and could not 12,13 . Although it is difficult to determine why the first study showed such a dramatic effect, its initial results are curious.…”
Section: Four Ways To Fight Noisementioning
confidence: 99%
“…;DLK WT (black), n = 21 (with none being censored). Log-rank test (*P = 0.0085) for the whole model, with a significant DLK genotype effect (**P = 0.0028); sex effect (not significant To determine whether the protection of motor neurons after Dlk deletion would provide lasting functional benefit, we examined symptom progression and life span in an independent cohort of SOD1 (34), including the wire hang test, a measure of motor strength (Fig. 4H and fig.…”
Section: G93amentioning
confidence: 99%